Penatalaksanaan Fisioterapi pada Kasus Trigger Finger Et Causa Tendinitis dengan Modalitas Ultrasound dan Terapi Latihan di RSUP. dr. Soetomo Surabaya - Vamula, Alfinta Septa; , Arif Pristianto, SSt.FT.,M.Fis (2015)
Background: Trigger finger is a condition when a finger seen broken or a movement that is not flat in the movement of fingers bending and straightening fingers. Patient will complained about pain in the affected part. This condition happens when a tendon swell and form lump called nodule and cause tendon 'squashed' on pulley tunnel. The effect of trigger finger is unknown or idiopathic. Modality given in this case is ultrasound and therapeutic exercise with evaluation instruments used that consist of Visual Analogue Scale for pain and goneometer for range of motion. Objectives: This scientific aims to determine the effect of ultrasound modality in reducing pain and the influence of therapeutic exercise modality in improving range of motion in Trigger Finger conditions. Results: After 6 treatments of therapy, it was that showed pain assessment in silent pain T0=0 became T6=0, tenderness T0=6,1 became T6=0,7 , motion pain T0=6,2 became T6=1,2. Increase range of motion metacarpophalangea T0=(S):8-0-63 become T6=(S):30-0-80, proximal joints interphalangea T0=(S):0-0-47 become T6=(S) 0-0-75, distal joints interphalangea T=(S):0-0-17 become T6=(S):0-0-37. Conclusions and suggestions: The usage ultrasound in physiotherapy modality could reduce pain in conditions trigger finger and the usage of therapeutic exercise modality could increase the range of motion in the DIP, PIP and MCP joints. In this case, the implementation of trigger finger reqwired cooperation between the physiotherapist with patients and medical teams or other health personnels, in order to achieve the maximum treatment results. Key words: Trigger Finger, US ,dan TL.